IMPLEMENTASI METODE PEMBIASAAN IBADAH DAN ADAB DALAM MENANAMKAN NILAI-NILAI AKHLAK MULIA PADA SISWA SDTQ IMAM ASY-SYAFI'I LUBUK BASUNG - Afdhallul Ramadhan; Afifudin Ahmad Robbaani; Muhammad Syukur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of habituation methods in worship and manners in instilling noble moral values among students at SDTQ Imam Asy-Syafi’i Lubuk Basung. This research employed a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, teachers, and students as the research subjects. The results of the study indicate that the habituation method of worship and manners has been routinely implemented through activities such as reciting prayers, performing congregational Dhuha prayer, reading the Qur’an, greeting others with salam, maintaining cleanliness, and cultivating polite and disciplined behavior. The implementation of this habituation method has had a positive impact on students’ moral development, such as improving discipline, responsibility, politeness, and worship habits in daily life. Supporting factors in implementing this method include cooperation among teachers, an Islamic school environment, and parental support, while the inhibiting factors include the lack of discipline among some students as well as the influence of the environment and technology.